The association between Children's sleep quality and juvenile idiopathic arthritis - Li, Linxia; Di, Yazhen; Liu, Zhanli; Hao, Zelin (Frontiers in Pediatrics, 2026)
ObjectiveTo investigate possible sleep disturbances in children with juvenile idiopathic arthritis (JIA).MethodsThis case-control investigation evaluated 48 JIA patients vs. 90 healthy controls through comprehensive clinical assessments. Disease activity was quantified using the Juvenile Arthritis Disease Activity Score (JADAS-27), while health-related quality of life was measured with the Child Health Questionnaire (CHQ-PF28). Pain intensity was assessed through dual Methods: Visual Analog Scale (VAS) and Wong Baker Faces Scale. Fatigue levels were evaluated via the Pediatric Quality of Life Inventory Multidimensional Fatigue Scale (PedsQL-MFS), and sleep quality was analyzed using both the Children's Sleep Habits Questionnaire (CSHQ) and Sleep Disturbance Scale for Children (SDSC). All statistical analyses were conducted in SPSS 26.0, employing independent t-tests for intergroup comparisons and Spearman correlation analysis for variable relationships.ResultsThe incidence of sleep disturbance was significantly higher in the JIA group (P < 0.01). CSHQ assessments reveal abnormal total scores and six subdomains (sleep duration, daytime sleepiness, etc.; all P < 0.05), with specific correlations: total scores link to disease activity (JADAS-27/AJC; P = 0.021–0.05), shortened sleep duration strongly associates with ESR/functional status (P = 0.002/0.006), and daytime sleepiness connects to physician global assessments (PGA/PGE; P = 0.017–0.029). SDSC evaluations indicate abnormalities in four domains (all P < 0.05), notably: night hyperhidrosis correlates with disease activity markers (P = 0.032–0.039), excessive sleepiness associates with fatigue/functional impairment (P = 0.014/0.038), and arousal disorders relate to medication use (P = 0.029).ConclusionsJIA patients show significantly higher rates of sleep disorders compared to healthy children, primarily due to disease activity, functional impairment, and medication effects.